PELATIHAN KEAMANAN PANGAN UNTUK PELAKU UMKM KECAMATAN TAMANSARI, KABUPATEN BOGOR - Pratiwi, Aprilianti; Sumiati, Yati; Fatika, Raisya Aliya; Artamevia, Monik (Jurnal Abdi Insani, 2024)
Food safety is an important aspect that must be carried out by food and beverage industry players, including MSME actors in Tamansari District, Bogor Regency. Although their potential in supplying local food is quite large, there are still serious challenges related to the understanding and application of good food safety principles. The lack of food safety by a number of MSME actors in Tamansari District not only affects the quality of the products they offer but also has an impact on consumer health and the sustainability of their businesses. The purpose of this community service activity is to provide knowledge and skills to MSME actors in Tamansari to be able to ensure that products are safe to consume and meet quality standards so that they can compete in a wider market. The methods applied in this service activity are preparation and planning, socialization of activities, implementation of training, discussion and evaluation as well as follow-up and continuous support. Community service activities were carried out on September 2, 2024 at the Tamansari District Hall, Bogor Regency, West Java. The results of this activity show an increase in understanding from Tamansari MSME actors, Bogor Regency regarding the importance of food safety practices, starting from the production process to product distribution. The increase in understanding of the importance of food safety practices is known from the results of the pre-test and post tests carried out. The actors of Tamansari, Bogor Regency MSMEs who participated in this training were also given an understanding to practice better hygiene standards and raw material handling, in order to improve the quality and safety of the products produced. This is expected to have a positive impact on consumer confidence and support the sustainability of their business in a more competitive market. The success of this community service activity shows the importance of this training so that MSME actors in Tamansari District can implement food safety in their production process.